PESANTREN DAN PERUBAHAN SOSIAL: OPTIMALISASI MODAL SOSIAL BAGI KEMAJUAN MASYARAKAT - Dakir Dakir; Umiarso Umiarso (UIN Raden Mas Said Surakarta, 2017)
Poverty is the social-human problem in Indonesia and in the world. Pesantren with its social capital was able to take a role for that encourages social change towards a better direction. This study is a critical study on the role of pesantren in the mobilization process of social values and norms so that it was able to make social change in the perspective of social capital. The result of the study shows that through its social capital, such as social networking and trust, pesantren was able to break through the backwardness of society into a better society. In fact, the direction of social change conducted by pesantren which is integrating the religious values with the various dimension of social lives, and based on the spirit then supported by the principle of trust, empirically all of these become the powerful basis for the professional relationship.Â